Implementation of Bali Local Cultural Values (Jengah, Taksu, and Menyamabraya) in Human Resources Practices Associated with Stress and Organizational Performance in Cooperatives in Bali - Ni wayan Sitiari; Luh Kade Datriani; I Made Suniastha Amerta (Faculty of Economics and Business Udayana University, 2023)
The purpose of this research is to find out and explain the implementation of Balinese cultural values in human resource practices associated with stress and organizational performance. Respondents are managers of cooperatives in Bali total of 79 people. The analysis technique uses the application of a PLS-based structural equation model or SEM (structural equation modeling). The results showed: The influence of HR practices that implement local Balinese cultural is negative and significant on work stress. The influence of the implementation of local cultural values on HR practices on organizational performance is positive and not significant.The effect of stress on organizational performance is increasing. positive and significant. So it is a finding in this study that the implementation of cultural values contained in the concepts of jengah, taksu, and menyamabraya to reduce stress and improve organizational performance. Employees feel no pressure because of the suitability of HR practices with their culture. Keyword: Cultural values (jengah, taksu, and meyamabraya) in HR practices, stress, and organizational performance